Colorimetria e cinetica di soluzioni di solfato di rame - Fortunato, Laura; Turturiello, Ilaria (Chimica nella Scuola, 2025)
Can the variation in the concentration of a CuSO4 solution be measured either as a change in absorbance or as a change in the color of the solution? Additionally, is measuring the temperature change during an exothermic reaction a good approach to study the kinetics of a reaction as the concentration of a reactant varies? These are the two research questions that emerged during laboratory activities with the students of class II A (CAT) at the IISS Cezzi De Castro Moro in Maglie (Lecce), which led to the scientific investigation presented in this work.